The Impact of Positive Verbal Rewards on Organizational Citizenship Behavior—The Mediating Role of Psychological Ownership and Affective Commitment - Zhao, Xin; Yang, Yi-chun; Han, Gexin; Zhang, Qiao (Frontiers in Psychology, 2022)
The organizational citizenship behavior (OCB) can foster organizational competitiveness and survival especially facing the rapid changing environment. There are some empirical research shed lights on the effects of organizational citizenship behavior on extrinsic rewards. Since OCB, through performance appraisal, affects extrinsic rewards which will influence OCB as well. However, researchers have overlooked the reverse effect of extrinsic rewards (i.e. positive verbal rewards) on organizational citizenship behavior. It is necessary to explore the mechanism between positive verbal rewards and OCB. This study integrated psychological ownership and affective commitment to form a structural model based on social exchange theory and cognitive evaluation theory. This results show that positive verbal rewards is positively correlated with psychological ownership, psychological ownership is positively correlated with affective commitment and OCB, and affective commitment is positively correlated with OCB. As refers to the mediating effects, psychological ownership fully mediates the relationship between positive verbal rewards and affective commitment. Furthermore, affective commitment plays a partial mediating role in the effect of psychological ownership on OCB. Accordingly, this psychological mechanism between positive verbal rewards and OCB reveal important theoretical and practical implications.